Experiences of Gen Zs in movement competency training course: basis for contextualizing the Philippine PATH-Fit - Tagare, Jr., Ruben L.; Saroca, Jr., Daniel B.; Aguinaldo, Jerrwin C.; Meriales, Rosalie D.; Lunag, Gliceria C.; Java, Vinus P.; Elumbaring, Jerum B.; Esto, Jomar B.; Janito, Cheeze R.; Nadela, Lara Ivanah C.; Esponja, Joanna Caryl P.; Martinez, Norge D; Calixtro, Marichu A.; Dee, Michelle R. (Journal of Education and Learning (EduLearn), 2026)
This study explored the experiences of Generation Z (Gen Z) students from rural communities in the PATH-Fit 1 course (movement competency training) to identify ways to improve the Philippine Physical Activity Toward Health and Fitness (PATH-Fit) program. A qualitative-descriptive approach was used, with 20 students carefully selected for interviews. Open-ended questions, validated by experts, were used to gather detailed insights into the students’ thoughts and experiences. The findings revealed that students enjoyed the engaging activities, the focus on overall well-being, and the supportive nature of their teachers in PATH-Fit 1. However, they also found the course physically exhausting and too demanding, which led to frustration. Additionally, students expressed concerns about teacher absenteeism and the ineffectiveness of online classes, which negatively impacted their learning experience. These issues highlighted areas where the program could be improved to better meet the needs of rural Gen Z students. By addressing these concerns, the PATH-Fit program can be more effectively tailored to enhance student engagement and learning outcomes, ultimately providing a more positive and fulfilling educational experience for Gen Z learners in rural communities.